DSL-Notch Signaling in the Drosophila Brain in Response to Olfactory Stimulation - Lieber, Toby; Kidd, Simon; Struhl, Gary (Neuron (Cambridge, Mass.), 2011)
Delta/Serrate/Lag2 (DSL) ligands and their Notch family receptors have profound and pervasive roles in development. They are also expressed in adult tissues, notably in mature neurons and glia in the brain, where their roles are unknown. Here, focusing on the sense of smell in adult Drosophila, we show that Notch is activated in select olfactory receptor neurons (ORNs) in an odorant-specific fashion. This response requires olfactory receptor activity and the Notch ligand Delta. We present evidence that Notch activation depends on synaptic transmission by the ORNs in which the receptors are active and is modulated by the activity of local interneurons in the antennal lobe. It is also subject to regulatory inputs from olfactory receptor activity in other ORNs. These findings identify a correlate of stimulus-dependent brain activity and potentially new forms of neural integration and plasticity. ► Notch is activated in fly olfactory receptor neurons (ORNs) in response to odors ► Activation requires olfactory receptors and signaling by the Notch ligand Delta ► Activity depends on synaptic transmission by ORNs and their interneuron partners ► Notch activity defines an engram of sensory experience and neural integration